Psychometric Properties of the Persian Version of Volitional Questionnaire in Patients with Severe Mental Illnesses - Moslem Cheraghifard; Narges Shafaroodi; Mitra Khalafbeigi; Farzaneh Yazdani; Faeze Alvandi (Shiraz University of Medical Sciences, 2019)
Background: The volitional questionnaire is an observational tool to assess motivation, which is based on the MOHO model and completed by an assessor based on the individuals' observation when performing an occupation or activity. The present study aims to translate and evaluate the validity and reliability of this instrument in individuals with severe mental illnesses and to provide an appropriate tool for volitional assessment. Methods: In this study, the volitional questionnaire was translated into Persian according to the IQOLA protocol. To assess the content validity, an expert panel was held with six experts. The face validity of the test was measured through completing a questionnaire by ten occupational therapists. To investigate the inter-rater reliability of the test, two testers completed the questionnaire for 30 individuals. The internal consistency of the instrument was calculated by performing the Cronbach's alpha coefficient, through completing the questionnaire for 98 individuals. Results: The participants in the expert panel stated that concept of motivation is properly reviewed by the items of questionnaire. All the questionnaire items had a significant important score of 0.7, indicating the suitability of its face validity. Inter-rater reliability (ICC = 0.93) was ideal, and the internal consistency of the questionnaire (Cronbach's α = 0.86) was appropriate. Conclusion: The questionnaire has desirable validity and reliability and can be used by specialists as a suitable tool for clinical evaluation and therapeutic planning of individuals with severe mental illnesses.